Innate lymphoid cells: Characterization and classification - Luci, Carmelo (2023)
Innate lymphoid cells (ILCs) are lymphocytes lacking the rearranged antigen receptors and mainly localized at epithelial surfaces, where they maintain tissue homeostasis, and provide a rapid response to pathogen assaults. ILCs share similarities with conventional T cells and are divided into 5 subsets based on cell surface markers, transcription factor requirement and ability to produce type 1, type 2 and Th17 cell-associated cytokines: conventional Natural Killer (NK) cells, helper ILC1, ILC2, ILC3 and Lymphocytes Tissue-Inducers (LTi) cells. They are endowed with a plasticity that allows them to modify their phenotype and their functionality to adapt to the microenvironment in which they are located. ILCs are considered resident cells in different peripheral tissues but they can also be present in lymph and peripheral blood as it is the case for NK cells. The description of the ILCs are complex and discordant since distinctive markers are either not supported in few tissues or across species and after inflammatory conditions. Today, to better understand the origin and classification of ILCs as a whole, and its participation in the immune response, it is necessary to unify criteria and nomenclature after comparing human and mouse recent studies...